Effectiveness of a mHealth Lifestyle Program With Telephone Support (TXT2BFiT) to Prevent Unhealthy Weight Gain in Young Adults: Randomized Controlled Trial - Partridge, Stephanie R; McGeechan, Kevin; Hebden, Lana; Balestracci, Kate; Wong, Annette TY; Denney-Wilson, Elizabeth; Harris, Mark F; Phongsavan, Philayrath; Bauman, Adrian; Allman-Farinelli, Margaret (JMIR Publications, 2015)
BackgroundWeight gained in young adulthood often persists throughout later life with associated chronic disease risk. Despite this, current population prevention strategies are not specifically designed for young adults. ObjectiveWe designed and assessed the efficacy of an mHealth prevention program, TXT2BFiT, in preventing excess weight gain and improving dietary and physical activity behaviors in young adults at increased risk of obesity and unhealthy lifestyle choices. MethodsA two-arm, parallel-group randomized controlled trial was conducted. Subjects and analyzing researchers were blinded. A total of 250 18- to 35-year-olds with a high risk of weight gain, a body mass index (BMI) of 23.0 to 24.9 kg/m2 with at least 2 kg of weight gain in the previous 12 months, or a BMI of 25.0 to 31.9 kg/m2 were randomized to the intervention or control group. In the 12-week intervention period, the intervention group received 8 text messages weekly based on the transtheoretical model of behavior change, 1 email weekly, 5 personalized coaching calls, a diet booklet, and access to resources and mobile phone apps on a website. Control group participants received only 4 text messages and printed dietary and physical activity guidelines. Measured body weight and height were collected at baseline and at 12 weeks. Outcomes were assessed via online surveys at baseline and at 12 weeks, including self-reported weight and dietary and physical activity measures. ResultsA total of 214 participants-110 intervention and 104 control-completed the 12-week intervention period. A total of 10 participants out of 250 (4.0%)-10 intervention and 0 control-dropped out, and 26 participants (10.4%)-5 intervention and 21 control-did not complete postintervention online surveys. Adherence to coaching calls and delivery of text messages was over 90%. At 12 weeks, the intervention group were 2.2 kg (95% CI 0.8-3.6) lighter than controls (P=.005). Intervention participants consumed more vegetables (P=.009), fewer sugary soft drinks (P=.002), and fewer energy-dense takeout meals (P=.001) compared to controls. They also increased their total physical activity by 252.5 MET-minutes (95% CI 1.2-503.8, P=.05) and total physical activity by 1.3 days (95% CI 0.5-2.2, P=.003) compared to controls. ConclusionsThe TXT2BFiT low-intensity intervention was successful in preventing weight gain with modest weight loss and improvement in lifestyle behaviors among overweight young adults. The short-term success of the 12-week intervention period shows potential. Maintenance of the behavior change will be monitored at 9 months. Trial RegistrationTrial Registration: The Australian New Zealand Clinical Trials Registry ACTRN12612000924853; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?ACTRN=12612000924853 (Archived by WebCite at http://www.webcitation.org/6Z6w9LlS9).